Testing the effects of Bdellovibrio on wheat (Triticum aestivum) and as a food security agent in mushrooms (Agaricus bisporus) - Saxon, Emma B. (2015)
Bdellovibrio bacteriovorus is a naturally soil-dwelling, Gram-negative predatory bacterium that attaches to, invades, and replicates within a wide range of other Gram-negative bacterial species, killing such prey in the process. A small number of previous studies testing the effect of B. bacteriovorus against known Gram-negative plant pathogens have suggested that B. bacteriovorus has potential as a ‘food security agent’ against Gram-negative bacterial infections in crop plants. My project built on this knowledge by screening a range of known Gram-negative bacterial plant pathogens and Plant Growth-Promoting Rhizobacteria (PGPRs) for susceptibility to Bdellovibrio predation in vitro; testing predation-susceptible strains in a simple, semi-sterile in vivo system on the surface of Agaricus bisporus mushrooms; and finally testing the effect of Bdellovibrio addition in a more complex, natural Triticum aestivum (wheat) soil rhizosphere mesocosm. An in vitro prey strain growth assay showed that susceptibility to B. bacteriovorus predation varied between a range of 20 Gram-negative (mostly Pseudomonas) bacterial pathogen/PGPR species, isolated from a range of different host crops or soil environments. Four of these species (Pseudomonas avellanae 48, P. syringae pv. phaseolicola, P. tolaasii 2192T and P. agarici 2289) were highly susceptible to predation, and three species (B. vietnamiensis G4, P. marginalis 667, and Pectobacterium atrosepticum SCRI1143) showed apparent resistance to predation. P. tolaasii 2192T, causes dark, pathogenic lesions on post-harvest mushroom host crops; In vivo co-inoculation tests on the surface of A. bisporus mushrooms showed that lesions were significantly reduced with B. bacteriovorus treatment, which was due to B. bacteriovorus predatory killing and reduction of prey cell numbers, preventing symptoms. B. bacteriovorus also preyed upon and killed a putative pathogenic Pseudomonas species isolated from a grey lesion on an organic, garden mushroom, but some likely commensal species isolated from mushroom tissue showed resistance to predation. These data together suggest that B. bacteriovorus could be used commercially to prolong the shelf life of mushrooms, reducing crop losses through spoilage, with minimal negative effects on mushroom PGPR species. Finally, inoculating B. bacteriovorus into the soil around young winter wheat plants in a natural pot soil mesocosm was found to increase plant growth and grain yield at harvest; this was contrary to my initial hypothesis that B. bacteriovorus would reduce wheat plant growth, by preying upon and killing PGPR species such as P. fluorescens that reduce wheat plant infection with Gaeumannomyces graminis var. tritici, the yield-reducing take-all fungal pathogen of wheat. The soil was found to be low in nitrogen; thus B. bacteriovorus inoculation could have increased wheat growth due to B. bacteriovorus death in the soil and subsequent release of nutrients including nitrogen. However, some B. bacteriovorus cells survived in the soil where they could prey upon some Gram-negative bacterial species, reducing their numbers. Some of the wheat growth and yield-producing effects of B. bacteriovorus may be due to the predation of species that are associated with late flowering, and therefore grain development, in wheat, allowing time for more grain to develop. Alternatively, it could be due to processes performed by B. bacteriovorus in the soil that are not related to predation, such as production of the plant hormone IAA, or B. bacteriovorus colonisation of the roots and predation of root-associated pathogenic bacterial species. Further studies are required to identify the mechanisms behind these unexpected crop yield-promoting effects, and the extent of any nutrient ‘boost’ effect due to death of B. bacteriovorus in the wheat soil, to determine whether B. bacteriovorus could be used as a pre-harvest growth and yield-promoting agent. Although most studies of B. bacteriovorus so far have focussed on its predatory activity, it likely performs other functions in its natural soil habitat, which may underlie some of the growth and yield-promoting effects shown here. However, these data show that B. bacteriovorus could be used commercially as a ‘food security agent’ when used as a post-harvest treatment to prevent crop spoilage and loss (as for A. bisporus mushrooms).